PENGEMBANGAN E-LKPD BERBASIS PLATFORM WIZER.ME PADA MATA PELAJARAN IPAS MATERI SISTEM PERNAPASAN MANUSIA SISWA KELAS V DI SDN GUGUS IV KECAMATAN SUKASADA - Komang Rista Apriani; I Made Sedana; IG Agung Jaya Suryawan (Widyajaya: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This research aims to develop teaching materials in the form of E-LKPD (Electronic Student Worksheets) based on the wizer.me platform for Natural and Social Sciences (IPAS) subject, specifically on human respiratory system material for fifth-grade students at Elementary Schools in Cluster IV, Sukasada District, which is valid and practical in enhancing students' interest and enthusiasm for learning. The background of this research is based on the lack of student activity and learning outcomes, limited interactive teaching materials, and suboptimal utilization of technology in the learning process. This research employs the ADDIE model, which is divided into five stages: Analysis, Design, Development, Implementation, and Evaluation. This E-LKPD has advantages including an attractive appearance, interactivity, easy access through various digital devices, and support for independent student learning. The research subjects consisted of 3 expert judges for instruments, 6 experts for product testing, 1 teacher with Master's degree at Grade IV civil service level, 4 teachers, and fifth-grade students at Elementary Schools in Cluster IV, Sukasada District. The data collection methods used include observation, interviews, and questionnaires/surveys. The research results show that the E-LKPD based on the wizer.me platform is assessed as highly valid with media validation scores of 0.93, material validation of 0.94, and language validation of 0.91. Meanwhile, the practicality test results by teachers and students obtained overall practicality results by teachers of 95.5% and assessment by students of 92%. This indicates that the developed product falls into the category of highly practical. Therefore, the E-LKPD based on the wizer.me platform is suitable for use as innovative teaching material to enhance student engagement in IPAS learning and support the achievement of learning objectives in the digital era.